Asymptomatic Urinary Tract Infection in Gynaecological Outpatients. Issue 5635 (4th January 1969) - Williams, J. D.; Thomlinson, J. L.; Cole, J. G. L.; Cope, E.
Abstract : In this study mid-stream specimens of urine were collected from all new patients attending a gynaecological outpatient department and tested for significant bacteriuria. Those having an asymptomatic infection were folloWed up, treated, and investigated adiologically. Of 1, 506 women screened for bacteriuria 82 (5·4%) were found to have a persistent infection. The predominant organism was Escherichia coli, present in 83% of infections. Treatment with sulphonamides produced a good cure rate, which was improved by ampicillin given to failures. Some patients, however, had infections that persisted or recurred despite several antibiotics. The radiological investigations showed that a high proportion of women with asymptomatic urinary infection had severe renal disease which was quite symptomless. This was more pronounced in those with persistent or recurrent infections.